Development of an Arduino-Based Microcontroller System to Maintain Temperature Stability in the Plastic Waste Pyrolysis Process - Siahaan, Enzo Wiranta Battra; Sitanggang, Hodmiantua; Sidabutar, Rotama Arifin (TEKNIK, 2025)
This study aims to develop and evaluate a temperature monitoring and control system for a plastic pyrolysis model operating within the temperature range of 400–500 °C. The system is designed using a microcontroller to read signals from 4 thermocouples placed at various points within the pyrolysis chamber. The collected temperature data are processed, displayed on an LCD screen, and stored on an SD card. Temperature control is carried out using a potentiometer, while data logging is managed through push-button switches. An electric heater is used as the heat source, controlled by a relay, and temperature readings are calibrated using a commercial thermometer to ensure accuracy. The test results indicate that the system is capable of consistently monitoring and maintaining temperatures within the specified range. Although temperature variations were observed at different measurement points, the system generally demonstrated good performance in temperature control. The system effectively approached the target temperature, though temperature deviations were still influenced by heating rate and thermocouple characteristics. Additionally, the observed uneven temperature distribution highlights the need for improvements in the heating system design to enhance thermal uniformity within the pyrolysis chamber.